วิเคราะห์บทละครประวัติศาสตร์ของหลวงวิจิตรวาทการ - ประอรรัตน์ บูรณมาตร์ (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
This thesis aims at studying Luang Vichit Vadaken’s historical plays, particularly in the light of the relationship between literature and society, as the political and social milieu under Field Marshal Phibulsongkram’s regime had an immense influence upon Luang Vichit’s plays and Luang Vichit’s plays, on the other hand, helped to shape concepts and patterns of thought of the public. To make the subject matter clear, the writer have divided the thesis into seven chapters. The first chapter introduces the problem. The second discusses the relationship between literature and society : how they influence each other. The third chapter probes into the two phases of Field Marshal Phibulsongkram’s policy to mobilize nationalism. The first phase of nationalism (2481 – 2487 B.E.) was the period of building great national power and cultural reformation. Then came the second phase of nationalism (2490 – 2500 B.E.) when the government felt the urge to emasculate Communism, a memacing threat to national security. Luang Vichit, as a politician, a historian, and a writer, played an impressive role in identifying himself voluntarily with the government’s policy of nationalism. Chapter four emphasizes the social forces which influenced Luang Vichit’s historical plays. In the first phases of nationalism and building great national power, Luang Vichit, then the Director of the Department of Fine Arts, was assigned to plant ‘Ton Rak Chat, (the Love Thy Nation plant) about his Department’s compound. He was so inspired that he wrote many historical plays, all of which concentrate on one single purpose – to arouse the patriotic sentiment among his audience. In the later phase of the government’s nationalistic policy, the plays served, to a larger extent, as an effective means to evoke public antagonism against the communists. More discussed in the chapter are some parts of social life under Premier Phibulsongkram as reflected in Luang Vichit’s historical plays. Chapter five analyses and evaluates Luang Vichit’s historical plays as literary art. Each play is examined in detail : genre, theme, plot, characterization, dramatization, setting and, most important, Luang Vichit’s effective technique of ‘sweetening the pill’ ; as the plays delight the heart with entertainment as well as they elevate the mind to patriotism. The distinctive features which made his plays most popular in his time are also discussed. Chapter six treats how Luang Vichit’s historical plays have affected his contemporary and today’s mind 2523 B.E. The plays had an immediate influence in ingraining patriotism among the public only before the Second World War, at the time Luang Vichit was the Director of the Department of Fine Arts. After the war, the plays were less popular, unable to maintain its grip on the public. Nevertheless, Luang Vichit’s historical plays, despite some imaginative exaggeration and distortion of fact to aggrandize the Thai nation, have played an important role in the comprehension of Thai history. Besides the immediate influence, is the residued influence Luange Vichit’s patriotic songs and Witty slogans from the plays have more or less clung on the lips of Thai people since Field Marshal Phibulsongkram’s rule until now. Especially at the times of national crisis when patriotism is an essential [equipment,] the songs and slogans are used again and again. They have become symbols of nationalism. Luang Vichit’s historical plays themselves have contributed to the conception of later historical plays. The last chapter gives the conclusion. The social circumstances under Premier Phibulsongkram played an influential role on Luang Vichit’s literary works : the governemnt’s policy inspired the main ideas of his historical plays ; the plays were used as implement to ingrain public nationalism, thus, were fully supported and fostered by the government. On the other hand, Luang Vichit’s historical plays have shown influence upon the people them and now. This study of Luang Vichit’s historical plays underlines the fact literature occurs in a social context, as a part of culture, in a social milieu, that it not merely reproduces life of the given society but also, more or less, helps to shape it. Hence, literature and society are two autonomies which are closely related to each other.